The expectations of pregnant women regarding antenatal care - JM Mathibe-Neke (AOSIS, 2008)
From a feminist perspective, research on childbirth and women's health is a means to a positive change that is conducted in partnership with women for their benefit. A patient-led National Health System (NHS) (Hillan, 1999) also calls for consultation with patients and the wider public for shaping the current and future health services. This study was aimed at exploring and describing the expectations that pregnant women have regarding antenatal care service by the midwife practitioner. In-depth interviews were conducted in an antenatal unit of an Academic Hospital in Gauteng Povince. Data saturation was reached with a sample of eighteen pregnant women who were conveniently selected. Data analysis ran concurrently with data collection. A manual content analysis as described by Tesch was used. Lincoln and Guba's method of ensuring trustworthiness was adopted (Lincoln & Guba, 1985:328)